OPTIMIZATION IN INVENTORY MANAGEMENT: Application of the ABC Curve in the stock of steel sheets of a road equipment manufacturer - Salatino, Guilherme Rafael; Ferrarezi Junior, Edemar (Revista Interface Tecnológica, 2024)
This article presents the application of the ABC Curve in the inventory management of steel plates in a manufacturer of road implements located in the interior of São Paulo. The main objective was to identify the most significant items in terms of cost and consumption, as well as to calculate the safety stock and replenishment point for these materials. The results showed that a small amount of materials is responsible for most of the costs, allowing the company to prioritize its efforts in the management of these items. The implementation of the ABC Curve, together with the calculations of safety stock and replacement point, contributed to a better organization and operational efficiency, reducing the risk of interruptions in the production process. This study highlights the importance of effective inventory management and suggests that similar analyses be carried out on other material groups to further enhance the company’s efficiency and competitiveness.